Biosseguridade para sistemas de produção de peixes em tanque-rede em função da colmatação agravada por Limnoperna Fortunei - Guilherme Rocha Vianna (2015)
The most consumed protein in the world is that from fish. Net pen fish aquaculture, a production system used worldwide, has been adapted to the Brazilian socio-environmental conditions to produce tropical fish in freshwater. Brazil has excellent conditions for aquaculture, as well as an abundant supply of corn and soybean for animal feed. The production of fish in net pens uses a high-density stocking system that is dependent on the renewal of large amounts of water. Therefore, the screens used in this system are expected to not only efficiently enable this renewal but also show durability and resistance, thus furnishing high biosafety and an appropriate cost-benefit ratio. A highly clogged screen due to the adhesion of invasive golden mussel, Limnoperna fortunei, decreases the water quality because of a low water renewal rate in the net pen. This greatly harms the growing fish, which become stressed, thus causing an increased risk of disease development and worsened zootechnical results, in turn affecting socio-economic and production issues. Given the importance of subject, the objectives of the present study were to evaluate the degree of clogging on wire mesh screens manufactured with different types of materials, the temporal dynamics of the development of clogging by Limnoperna fortunei, and the cost-benefit ratio of the different materials used. The experiment examined screens of single-twist 19 mm mesh (NBR 10.118) made with five different types of wires: PVC-coated galvanized wire, PVC-coated galvanized wire with antifouling paint, Bezinal wire (bimetallic zinc aluminium alloy), thin stainless steel wire, and thick stainless steel wire. One hundred and sixty screen samples32 of each wire type (30 cm wide and 200 cm long)were placed in the lake of the Salto Caxias dam in the Iguaçu River, Paraná State, Brazil, between July 2012 and July 2014. Forty samples (8 of each type) were removed every 6 months to evaluate the weight gain due to screen clogging and to count the number of mussels on each screen. The difference in weight gain among the screen types was determined using descriptive analysis and the analysis of variance between groups applying the Kruskal-Wallis test. This study confirmed that the different wires used to construct the net pen screens influenced golden mussel adhesion to the screens and screen clogging. The tests indicated that the plasticised galvanized wire and thin and thick stainless steel wires had the highest levels of clogging and adhesion by the golden mussel, with statistically similar results. The Bezinal wire and plasticised galvanized wire covered with antifouling paint also showed statistically similar clogging and golden mussel adhesion levels. The most efficient screen in the net pen production system on a cost-per-year basis was the one using plasticised galvanized wire, the most efficient for low clogging used the Bezinal wire, and the most efficient for durability used the thin stainless steel wire.